PENGARUH KEBIJAKAN DIVIDEN DAN PERENCANAAN PAJAK TERHADAP RETURN SAHAM - Goinones, Laoren Agustin; Ridwan, Muhammad (LPPM Universitas Bina Bangsa, 2024)
This study aims to identify the influence of dividend policy and tax planning on stock returns. This research is a type of quantitative research conducted through the analysis of the financial statements of companies in the energy sector listed on the Indonesia Stock Exchange (IDX) throughout the period 2019 to 2022. The number of samples used in this study is 72 samples from 18 energy companies listed on the Indonesia Stock Exchange through the use of the purposive sampling method and tested with Eviews12. The data used in this study is secondary data in the form of financial statements from each company that has become a research sample. The results of this study show that the Dividend Policy partially affects Stock Return and Tax Planning has no effect on Stock Return. Meanwhile, at the same time, Dividend Policy and Tax Planning have an effect on Stock Returns. The contribution of the research to the variables of Dividend Policy and Tax Planning on Stock Returns is 30%, while the remaining 70% is explained by other variables outside the research model. Keywords: Dividend Policy; tax planning; Return on Stock